1994
DOI: 10.1080/09712119.1994.9706025
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Swine Waste by House-Fly Larvae and Evaluation of Their Protein Quality in Rats

Abstract: Iiiiguez-Covarrubias, G., F'ranco-G6mez, Ma, de J. and AndradeMaldonado, Gpe. del R. 1994. Biodegradation of swine waste by house fly larvae and evaluation of their protein quality in rats. J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Given the high forage and food value of Musca domestica, the cultivation of their larvae and pupae can alleviate the protein feed shortage (Akpodiete et al, 1997;Hwangbo et al, 2009;Iniguez-covarrubias et al, 1994;Miller et al, 1974;Ocio and Vinaras, 1979;van Huis, 2013;Yan et al, 2012;Zuidhof et al, 2003). Additionally, M. domestica larvae, or maggots, contain several biologically active substances, such as antimicrobial peptides, lectin and chitin Fu et al, 2009;Hou et al, 2007;Nayduch and Joyner, 2013;Tang et al, 2009;Wang et al, 2013;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Given the high forage and food value of Musca domestica, the cultivation of their larvae and pupae can alleviate the protein feed shortage (Akpodiete et al, 1997;Hwangbo et al, 2009;Iniguez-covarrubias et al, 1994;Miller et al, 1974;Ocio and Vinaras, 1979;van Huis, 2013;Yan et al, 2012;Zuidhof et al, 2003). Additionally, M. domestica larvae, or maggots, contain several biologically active substances, such as antimicrobial peptides, lectin and chitin Fu et al, 2009;Hou et al, 2007;Nayduch and Joyner, 2013;Tang et al, 2009;Wang et al, 2013;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…The supplemental use of maggots in animal feed may improve animals' immune systems and reduce antibiotic usage Dong et al, 2013). Excitingly, there have been reports on the culture of housefly-maggot in feces (Amano, 1985;Golubeva, 1986;Iniguez-covarrubias et al, 1994;Larrain and Salas, 2008). Moreover, manure of poultry and pig that has been treated with maggots becomes somewhat granular, which is suitable for further composting without bulking agents (Miller et al, 1974;Zhu et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…To fight this pest, facilities for mass rearing hymenopteran parasitoids on live or dead housefly hosts (pupae) have been set up to help reduce wild populations of houseflies (Morgan, 1986;Floate et al, 2002). However, some studies have shown that houseflies may also be used to decompose organic waste from livestock facilities (Miller et al, 1974;Iñiguez-Covarrubias et al, 1994;Barnard et al, 1998;Čičková et al, 2012). Housefly larvae readily feed on animal waste, transforming it into valuable feed and fertilizer (Téguia et al, 2002;Agunbiade et al, 2007;Ogunji et al, 2008;Kováčik et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The great number of flies needed to catabolize a reasonable amount of manure and the large space needed for biodegradation still pose problems [7] , [24] , [25] . Rearing of large numbers of houseflies has been limited to artificial media and the use of resulting pupae as hosts for hymenopteran parasitoids [26] .…”
Section: Introductionmentioning
confidence: 99%